Zoom Video Conference: Is It The Best Solution for Remote Learning of English Language Teaching? - Bina Wahyuni; Fatma Oryza; Wanda Putri Aulia (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2022)
COVID-19 pandemic has forced many innovations to support remote teaching and learning. With several means available to conduct the teaching and learning, Zoom has become the favorable one. This study investigates how students perceive Zoom as a video conference in English language learning. A survey quantitative method was used to generate the high school students’ perceptions. After distributing the questionnaire, the data was analyzed using descriptive statistics. The result shows that although the difference is not much, students gave more positive statements on the use of Zoom. This positive experience has proved that Zoom might be the best solution for English remote learning.